Co-Cr-Fe-Ni series ODS high-entropy alloy and preparation method and application thereof
The Co-Cr-Fe-Ni-based ODS high-entropy alloy is printed and annealed through SLM technology, which solves the problems of long cycle and low efficiency of traditional ODS alloy preparation process, realizes the efficient manufacturing of ODS high-entropy alloys and the preparation of complex components, and improves the comprehensive mechanical properties of the materials.
Patent Information
- Application Number
- CN202510052628.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The traditional oxide dispersion strengthening (ODS) alloy preparation process has problems such as long periods, low efficiency, easy contamination and difficulty in preparing complex components, which limits the production and application of ODS high-entropy alloys.
Selective laser melting (SLM) technology was used to prepare the FCC structure Co-Cr-Fe-Ni-based ODS high-entropy alloy. By fully mixing the Co-Cr-Fe-Ni high-entropy prealloy powder, Fe-Y prealloy powder and nanoTiO2 powder, and printing and forming in the SLM device, annealing treatment was performed to form uniformly distributed nanooxide particles.
It realizes efficient manufacturing of ODS high-entropy alloys, shortens the process cycle, improves the comprehensive mechanical properties of the materials, and can prepare complex components, solving the problem that traditional processes are difficult to prepare complex shapes.
Smart Images

Figure CN119913410A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal matrix composite materials, and in particular to a Co-Cr-Fe-Ni series ODS high entropy alloy and a preparation method and application thereof. Background Art
[0002] High entropy alloy is a new type of multi-principal alloy with broad application prospects in aerospace, new energy and biomedical fields. Among them, FCC high entropy alloy, as the earliest developed and deeply studied system, has excellent plasticity, toughness, thermal stability and good oxidation resistance, but its development and application are limited due to its relatively low hardness and strength at room temperature.
[0003] Oxide dispersion strengthening (ODS) is an important means of strengthening metals. Oxide particles (such as Y2O3) with high thermodynamic stability, high number density and only a few nanometers or tens of nanometers in size are evenly distributed in ODS alloys. These particles improve the strength of the material by pinning grain boundaries and dislocations. Introducing the ODS design concept into FCC high entropy alloys is expected to make up for their lack of room temperature strength and hardness, and enable them to obtain more excellent comprehensive mechanical properties.
[0004] At present, ODS alloys are mostly prepared by mechanical alloying (MA), which uses the long-term collision and extrusion of grinding media (usually grinding balls) and powders placed in a grinding container to break and re-weld the powders at the atomic level, promote the mutual diffusion and solid solution of the elements in the powders to form a supersaturated solid solution, and then solidify and heat treat to precipitate nano-oxide particles from the matrix in situ to obtain ODS alloys. During the ball milling process, since atoms diffuse in the solid phase, it generally takes dozens of hours or even hundreds of hours to form a supersaturated solid solution, and the subsequent solidification forming process is generally difficult to directly prepare complex components. Therefore, the problems of MA long process, low efficiency, easy pollution, and limited product size and shape have greatly restricted the production and application of ODS alloys.
[0005] With the rise of additive manufacturing technology, the preparation and forming of metal materials have ushered in new breakthroughs. Selective Laser Melting (SLM) is one of the most widely used and most promising technologies in the field of additive manufacturing. The main process flow of this technology can be divided into two stages: data processing and processing and manufacturing. The main work of the data processing stage is to use computer software to complete the modeling of the parts to be processed. In the processing and manufacturing stage, a thin layer of powder is evenly laid on the forming substrate and a high-energy laser beam is used to scan the powder according to the specified path and process parameters. Then the forming substrate is lowered by one layer and the powder laying and laser scanning are repeated to make the metal accumulate layer by layer, and finally the structural parts are obtained. Compared with traditional methods such as MA, this technology can obtain complex components with high precision, good surface quality and excellent mechanical properties, which greatly improves work efficiency. Therefore, the present invention provides a method for preparing FCC structure Co-Cr-Fe-Ni system ODS high entropy alloy by SLM. Summary of the invention
[0006] In view of the defects of the prior art, the purpose of the present invention is to provide a method for preparing FCC structure Co-Cr-Fe-Ni series ODS high entropy alloy by SLM. The method uses Co-Cr-Fe-Ni high entropy pre-alloy powder, Fe-Y pre-alloy powder, and nano-TiO2 powder as raw materials, and after fully mixing, uses SLM technology to print out bulk materials, and anneals them. The present invention uses SLM forming technology to prepare ODS high entropy alloys, which is expected to provide experimental basis and application foundation for the efficient manufacture of ODS high entropy alloys.
[0007] The technical solution of the present invention is achieved as follows: The present invention provides a Co-Cr-Fe-Ni series ODS high entropy alloy, wherein the Co-Cr-Fe-Ni series ODS high entropy alloy is obtained by SLM forming a mixed raw material powder consisting of Co-Cr-Fe-Ni high entropy pre-alloy powder, Fe-Y powder and TiO2 powder;
[0008] The elements Co, Cr, Fe and Ni in the Co-Cr-Fe-Ni high entropy pre-alloyed powder are in equal atomic ratios;
[0009] Among the raw materials, the proportion of Fe-Y powder is 0.7-2.0wt.%, the proportion of TiO2 powder is 0.8-2.4wt.%, and the proportion of Co-Cr-Fe-Ni high entropy pre-alloyed powder is 95.6-98.5wt.%.
[0010] On the basis of the above technical scheme, preferably, in the raw materials, the ratio of Fe-Y powder is 1.0wt.%, the ratio of TiO2 powder is 1.2wt.%, and the ratio of Co-Cr-Fe-Ni high entropy pre-alloyed powder is 97.8wt.%.
[0011] On the basis of the above technical solution, preferably, the content of Y element in the Fe-Y powder is 6.0wt.%.
[0012] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned Co-Cr-Fe-Ni based ODS high entropy alloy, comprising the following steps:
[0013] Step S1: using Co-Cr-Fe-Ni high entropy pre-alloyed powder, Fe-Y powder and TiO2 powder as raw materials, mixing them to obtain a mixed powder;
[0014] Step S2: forming the mixed powder by SLM printing and annealing to obtain the Co-Cr-Fe-Ni based ODS high entropy alloy.
[0015] On the basis of the above technical solution, preferably, in the step S2, the annealing gas is an inert gas, and the inert gas is selected from at least one of argon, helium and neon.
[0016] On the basis of the above technical solution, preferably, the annealing temperature is 800-950° C., and the annealing time is 1-2 hours.
[0017] On the basis of the above technical solution, preferably, the annealing temperature is independently selected from any value of 800°C, 820°C, 850°C, 880°C, 900°C, 950°C or a range between any two of the above.
[0018] On the basis of the above technical solution, preferably, the annealing time is independently selected from any value of 1h, 1.2h, 1.5h, 1.8h, 2h or a range between any two of the above.
[0019] On the basis of the above technical solution, preferably, the heating rate of the annealing is 10-15° C. / min.
[0020] On the basis of the above technical solution, preferably, in the step S2, the mixed powder is dried before SLM printing.
[0021] On the basis of the above technical solution, preferably, the drying temperature is 120-130° C., and the drying time is 20-30 hours.
[0022] On the basis of the above technical scheme, preferably, in step S2, the process parameters of the SLM printing forming are set as follows: the powder layer thickness is a fixed value of 40 μm, the scanning mode is a layer-by-layer rotation of 67°, the laser power is 200-300 W, the scanning interval is 70-80 μm, and the scanning speed is 600-1200 mm / s.
[0023] On the basis of the above technical solution, preferably, in step S2, the substrate formed by SLM printing is a stainless steel substrate, and the size of the substrate is 100 mm×100 mm.
[0024] On the basis of the above technical solution, preferably, the substrate is preheated to 120° C. before printing, and then vacuumed and filled with argon for protection, and formal printing is started after the oxygen content drops below 0.01%.
[0025] On the basis of the above technical solution, preferably, in step S1, a planetary ball mill is used for mixing, and no grinding balls or process control agents are added to the ball mill.
[0026] On the basis of the above technical solution, preferably, the rotation speed of the planetary ball mill is 200 rpm to 250 rpm, and the operation time is 4 to 6 hours.
[0027] On the basis of the above technical solution, preferably, the protective gas during the mixing is argon, and the amount of the argon is 0.1MPa to 0.15MPa.
[0028] On the basis of the above technical solution, preferably, in the step S1, during the ball milling, the ball mill jar is sealed and then evacuated using a vacuum pump, and then filled with 0.1 MPa argon as a protective gas, without adding any grinding balls or process control agents.
[0029] According to another aspect of the present invention, there is provided an application of the above-mentioned Co-Cr-Fe-Ni based ODS high entropy alloy and the Co-Cr-Fe-Ni based ODS high entropy alloy prepared by the above-mentioned preparation method in metal-based composite materials, aerospace, new energy, and biomedical fields.
[0030] As an optional implementation mode, the present invention is implemented by the following technical solution:
[0031] A method for preparing a Co-Cr-Fe-Ni based ODS high entropy alloy comprises the following steps:
[0032] S1. preparing a mixture of raw material powders of Co-Cr-Fe-Ni based ODS high entropy alloy;
[0033] S2. The mixed powder is subjected to SLM forming to prepare a Co-Cr-Fe-Ni based ODS high entropy alloy bulk material, and the bulk material is subjected to annealing heat treatment to obtain a Co-Cr-Fe-Ni based ODS high entropy alloy.
[0034] Optionally, in step S2, before performing the SLM forming technology, the mixed powder is first placed in a vacuum drying oven and kept warm at 120° C. for 20 hours, and then the mixed powder is taken out and poured into a powder feeding bin of a printing device and flattened.
[0035] Optionally, in step S2, the substrate of the printing device adopts a stainless steel substrate with a size of 100 mm×100 mm. After the substrate is installed in the printing device, it is preheated to 120° C., and then the printing device is vacuumed and filled with high-purity argon as a protective gas. Printing is officially started when the oxygen content in the device drops below 0.01%.
[0036] Optionally, in step S2, the basic process parameters of the SLM forming technology are set as follows: the powder layer thickness is a fixed value of 40 μm, a scanning strategy of rotating 67° layer by layer is adopted, the laser power is 200-300 W, the scanning spacing is 70-80 μm, and the scanning speed is 600-1200 mm / s.
[0037] On the one hand, the present invention utilizes a laser heat source to completely melt the mixed powder to form a high-entropy alloy system rich in Y, Ti, and O. A portion of the Y, Ti, and O elements directly react in situ during the solidification and cooling process to form a Y-Ti-O composite oxide with higher thermal stability than Y2O3. Since the molten pool is small and the solidification and cooling speed is fast during the SLM forming process, the agglomeration and growth of the nano-oxide particles are inhibited, which can ensure that the nano-particles in the bulk alloy are small in size and evenly distributed. At the same time, the bulk alloy obtained by printing is further annealed to promote more Y, Ti, and O elements to precipitate in situ from the matrix in the form of nano-oxide particles. The dispersion strengthening effect of the precipitated nano-oxide particles can improve the comprehensive mechanical properties of the high-entropy alloy, further ensuring that the nano-particles in the ODS high-entropy alloy have a higher number density.
[0038] On the other hand, the present invention utilizes the advantages of SLM such as no need for molds and high forming efficiency to achieve direct rapid forming of ODS high entropy alloy, solving the problems of long cycle, multiple processes and difficulty in preparing complex components in the preparation of ODS alloys using traditional powder metallurgy technology (such as MA).
[0039] The Co-Cr-Fe-Ni system ODS high entropy alloy of the present invention has the following beneficial effects compared with the prior art:
[0040] (1) The existing MA method for preparing ODS alloys requires high-energy ball milling of the raw material powder for dozens or even hundreds of hours to obtain a supersaturated solid solution, which is time-consuming, prone to pollution, and inefficient. The present invention only requires a short mixing of the raw material powder to obtain a mixed powder that is directly used in the SLM process, which has a short process time, is not prone to pollution, and is highly efficient.
[0041] (2) The present invention uses Co-Cr-Fe-Ni high entropy pre-alloy powder, Fe-Y pre-alloy powder, and nano-TiO2 powder as raw materials for mixing. The mixed powder is completely melted in the SLM process, so that the Y, Ti, and O elements can form Y-Ti-O particles through in-situ reaction during the solidification and cooling process of SLM. The Y-Ti-O particles are more stable than Y2O3 and are generally smaller in size.
[0042] (3) The present invention uses SLM additive manufacturing technology to gradually form the required metal components under the control of a computer program, without the need for molds, and achieves near-net-shape formation, thus solving the problem that the existing powder metallurgy technology is difficult to prepare complex ODS alloy components.
[0043] (4) The present invention adopts SLM additive manufacturing technology. The molten pool formed by the laser heat source is small and the solidification speed of the molten pool is fast, which can inhibit the agglomeration and growth of oxide particles and obtain an ODS high entropy alloy block with uniform distribution of nano-oxide particles.
[0044] (5) The present invention further performs annealing treatment on the printed bulk alloy to promote the in-situ precipitation of more nano-oxide particles from the matrix, so that the nano-particles in the ODS high entropy alloy have a higher number density. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0046] Figure 1 Flow chart of the preparation method of Co-Cr-Fe-Ni based ODS high entropy alloy provided in an embodiment of the present invention;
[0047] Figure 2 This is a scanning electron microscope photograph of the Co-Cr-Fe-Ni based ODS high entropy alloy after being corroded by aqua regia in Example 1 of the present invention;
[0048] Figure 3 This is a HAADF-STEM photograph of the Co-Cr-Fe-Ni based ODS high entropy alloy in Example 1 of the present invention under a transmission electron microscope;
[0049] Figure 4 This is a scanning electron microscope photograph of the alloy in Comparative Example 1 of the present invention after being corroded by aqua regia. DETAILED DESCRIPTION
[0050] The technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The SLM forming technology disclosed in the present invention has great advantages in the preparation of processed material parts because of its advantages such as fast processing efficiency, few and convenient post-processing steps, and the formed materials usually have a fine organizational structure. It is expected to become a new process for preparing ODS high entropy alloys. Therefore, the present invention adopts the solution of preparing ODS high entropy alloys using SLM forming technology, hoping to provide experimental basis and application basis for preparing ODS high entropy alloys using SLM forming technology.
[0051] Specifically, using Figure 1 The preparation steps shown are for preparing Co-Cr-Fe-Ni based ODS high entropy alloy, including:
[0052] S1. Preparation of Co-Cr-Fe-Ni ODS high entropy alloy raw material powder
[0053] S1.1. Composition design and ingredients
[0054] Co-Cr-Fe-Ni high entropy pre-alloy powder, Fe-Y pre-alloy powder and nano-TiO2 powder are uniformly mixed as raw materials in a certain proportion. Preferably, the ratio of Co-Cr-Fe-Ni high entropy pre-alloy powder is 97.8wt.%, the ratio of Fe-Y powder is 1.0wt.%, and the ratio of TiO2 powder is 1.2wt.%.
[0055] Preferably, the elements in the Co—Cr—Fe—Ni high entropy pre-alloyed powder are in equiatomic ratios, and the content of Y element in the Fe—Y powder is 6.0 wt.%.
[0056] S1.2, Powder mixing
[0057] Use an electronic balance to weigh the required raw material powders according to the above ratio, mix the weighed powders and pour them into a stainless steel ball mill. After the ball mill is sealed, use a vacuum pump to evacuate, and then fill it with 0.1MPa argon as a protective gas without adding any grinding balls or process control agents. Use a planetary ball mill to run at a speed of 200rpm for 6h so that all kinds of powders in the mixed powder can be evenly mixed, thereby obtaining a mixed powder for the SLM process.
[0058] S2. Preparation of Co-Cr-Fe-Ni ODS high entropy alloy blocks by SLM forming
[0059] S2.1. Pre-forming treatment
[0060] Before printing begins, the raw material powder is placed in a vacuum drying oven and kept at 120°C for 20 hours, then the raw material powder is taken out and poured into the powder feeding bin of the printing device and laid flat. After the stainless steel substrate is installed in the printing device, it is preheated to 120°C, and then the printing device is vacuumed and filled with high-purity argon as a protective gas. Printing officially begins when the oxygen content in the device drops below 0.01%.
[0061] S2.2, SLM forming
[0062] The ODS high entropy alloy block material was prepared using SLM forming technology. After printing, it was separated from the substrate using wire cutting equipment.
[0063] Preferably, the process parameters of the SLM printing are: powder layer thickness of 40 μm; laser power of 200W-300W; scanning spacing of 70 μm-80 μm; scanning speed of 600-1200 mm / s. In order to reduce the thermal stress of the component, the scanning strategy adopts layer-by-layer rotation of 67° scanning (that is, the scanning angle of each continuous layer needs to be rotated 67° in the same direction).
[0064] S3. Performing annealing heat treatment on the bulk material.
[0065] The ODS high entropy alloy bulk materials prepared by SLM were annealed in a tubular furnace under argon protection.
[0066] Preferably, the annealing temperature is 900° C., the holding time is 1 h, and the heating rate is set to 10° C. / min.
[0067] The above technical solution is described in detail below in conjunction with specific embodiments.
[0068] Example 1
[0069] This embodiment provides a SLM preparation method of a Co-Cr-Fe-Ni based ODS high entropy alloy, which is as follows:
[0070] (1) Co-Cr-Fe-Ni high entropy pre-alloyed powder with equal atomic ratios of each element, Fe-Y pre-alloyed powder containing 6.0wt.% Y element, and TiO2 powder are used as raw materials. The required powders are weighed according to the ratio of 97.8wt.% Co-Cr-Fe-Ni, 1.0wt.% Fe-Y, and 1.2wt.% TiO2. The weighed powders are mixed and poured into a stainless steel ball mill with a volume of 500ml (400g mixed powder per can). After the ball mill is sealed, it is vacuumed using a vacuum pump, and then filled with 0.1MPa argon as a protective gas without adding any grinding balls or process control agents. Then a planetary ball mill is used to operate at a speed of 200rpm for 6h so that the various powders in the mixed powder can be evenly mixed, thereby obtaining a raw material mixed powder for the SLM process. The raw material mixed powder is placed in a vacuum drying oven and kept warm at a temperature of 120℃ for 20h, and then the raw material mixed powder is taken out and poured into the powder feeding bin of the printing device and flattened. A 100 mm × 100 mm stainless steel substrate was installed in the printing device and preheated to 120°C.
[0071] (2) The basic SLM process parameters were set as follows: powder layer thickness of 40 μm, laser power of 200 W, scanning spacing of 70 μm, and scanning speed of 800 mm / s. The printing equipment was evacuated and filled with high-purity argon as a protective gas. Printing began when the oxygen content in the equipment dropped below 0.01%. After printing, a 5 mm × 8 mm × 10 mm rectangular sample was obtained, and the printed sample was separated from the substrate by wire cutting.
[0072] (3) Each ODS high entropy alloy block material prepared by SLM was annealed in a tube furnace under argon protection. The annealing temperature was 900°C, the holding time was 1h, and the heating rate was set to 10°C / min.
[0073] Determination by density balance and Vickers hardness tester showed that the Co-Cr-Fe-Ni based ODS high entropy alloy block had good forming performance, a density of 98.4% and a hardness of 270.5 HV. Figure 2 This is a scanning electron microscope (SEM) photograph of the alloy after aqua regia corrosion. The molten pool boundary and the substructure within the grains can be clearly seen, and there are no other impurity phases in the sample. Figure 3 This is the HAADF-STEM photo of the alloy under a transmission electron microscope. It can be observed that a large number of nanoparticles (black particles in the figure) are dispersed in the matrix, with an average size of about 7nm and a number density of about 7.6×10 22 m -3 After calibration, these nanoparticles were identified as Y2Ti2O7.
[0074] Example 2
[0075] This embodiment provides a SLM preparation method of a Co-Cr-Fe-Ni based ODS high entropy alloy, which is as follows:
[0076] (1) Co-Cr-Fe-Ni high entropy pre-alloyed powder with equal atomic ratios of each element, Fe-Y pre-alloyed powder containing 6.0wt.% Y element, and TiO2 powder are used as raw materials. The required powders are weighed according to the ratio of 97.8wt.% Co-Cr-Fe-Ni, 1.0wt.% Fe-Y, and 1.2wt.% TiO2. The weighed powders are mixed and poured into a stainless steel ball mill with a volume of 500ml (400g mixed powder per can). After the ball mill is sealed, it is vacuumed using a vacuum pump, and then filled with 0.15MPa argon as a protective gas. No grinding balls or process control agents are added. Then a planetary ball mill is used to operate at a speed of 250rpm for 4h so that the various powders in the mixed powder can be evenly mixed, thereby obtaining a raw material mixed powder for the SLM process. The raw material mixed powder was placed in a vacuum drying oven and kept at 130°C for 30 hours, then the raw material mixed powder was taken out and poured into the powder feeding bin of the printing device and laid flat. The 100mm×100mm stainless steel substrate was installed in the printing device and preheated to 120°C.
[0077] (2) The basic SLM process parameters were set as follows: powder layer thickness of 40 μm, laser power of 200 W, scanning spacing of 80 μm, and scanning speed of 600 mm / s. The printing equipment was evacuated and filled with high-purity argon as a protective gas. Printing began when the oxygen content in the equipment dropped below 0.01%. After printing, a 5 mm × 8 mm × 10 mm rectangular sample was obtained, and the printed sample was separated from the substrate by wire cutting.
[0078] (3) Perform annealing heat treatment on the printed alloy in the same manner as step (3) of Example 1.
[0079] The Co-Cr-Fe-Ni based ODS high entropy alloy has good bulk forming performance, a density of 98.7%, and a hardness of 261.7 HV. The microstructure of the alloy is similar to that of Example 1, and a large number of Y2Ti2O7 nanoparticles are dispersed in the matrix.
[0080] Example 3
[0081] This embodiment provides a SLM preparation method of a Co-Cr-Fe-Ni based ODS high entropy alloy, which is as follows:
[0082] (1) Co-Cr-Fe-Ni high entropy pre-alloyed powder with equal atomic ratios of each element, Fe-Y pre-alloyed powder containing 6.0wt.% Y element, and TiO2 powder are used as raw materials. The required powders are weighed according to the ratio of 97.8wt.% Co-Cr-Fe-Ni, 1.0wt.% Fe-Y, and 1.2wt.% TiO2. The weighed powders are mixed and poured into a stainless steel ball mill with a volume of 500ml (400g mixed powder per can). After the ball mill is sealed, it is vacuumed using a vacuum pump, and then filled with 0.12MPa argon as a protective gas. No grinding balls or process control agents are added. Then a planetary ball mill is used to operate at a speed of 220rpm for 5h so that the various powders in the mixed powder can be evenly mixed, thereby obtaining a raw material mixed powder for the SLM process. Put the raw material mixed powder into a vacuum drying oven and keep it at 125℃ for 25h, then take out the raw material mixed powder and pour it into the powder feeding bin of the printing equipment and spread it flat. Install the 100mm×100mm stainless steel substrate in the printing equipment and preheat it to 120℃.
[0083] (2) The basic process parameters of SLM were set as follows: powder layer thickness of 40 μm, laser power of 200 W, scanning spacing of 80 μm, and scanning speed of 1200 mm / s. The printing equipment was evacuated and filled with high-purity argon as a protective gas. Printing began when the oxygen content in the equipment dropped below 0.01%. After printing, a 5 mm × 8 mm × 10 mm rectangular sample was obtained, and the printed sample was separated from the substrate by wire cutting.
[0084] (3) Perform annealing heat treatment on the printed alloy in the same manner as step (3) of Example 1.
[0085] The Co-Cr-Fe-Ni based ODS high entropy alloy has good bulk forming performance, a density of 98.7%, and a hardness of 265.1 HV. The microstructure of the alloy is similar to that of Example 1, and a large number of Y2Ti2O7 nanoparticles are dispersed in the matrix.
[0086] Example 4
[0087] This embodiment provides a SLM preparation method of a Co-Cr-Fe-Ni based ODS high entropy alloy, which is as follows:
[0088] (1) Prepare raw material mixed powder and perform pre-printing preparation in the same manner as step (1) of Example 1.
[0089] (2) The basic process parameters of SLM were set as follows: powder layer thickness of 40 μm, laser power of 300 W, scanning spacing of 80 μm, and scanning speed of 800 mm / s. The printing equipment was evacuated and filled with high-purity argon as a protective gas. Printing began when the oxygen content in the equipment dropped below 0.01%. After printing, a 5 mm × 8 mm × 10 mm rectangular sample was obtained, and the printed sample was separated from the substrate by wire cutting.
[0090] (3) Perform annealing heat treatment on the printed alloy in the same manner as step (3) of Example 1.
[0091] The Co-Cr-Fe-Ni based ODS high entropy alloy has good bulk forming performance, a density of 98.5%, and a hardness of 265.0 HV. The microstructure of the alloy is similar to that of Example 1, and a large number of Y2Ti2O7 nanoparticles are dispersed in the matrix.
[0092] Example 5
[0093] (1) Using Co-Cr-Fe-Ni high entropy pre-alloyed powder with equal atomic ratios of each element, Fe-Y pre-alloyed powder containing 6.0wt.% Y element, and TiO2 powder as raw materials, the required powders are weighed according to a ratio of 95.6wt.% Co-Cr-Fe-Ni, 2.0wt.% Fe-Y, and 2.4wt.% TiO2, and the weighed powders are mixed and poured into a stainless steel ball mill with a volume of 500ml (400g of mixed powder per mill); the remaining preparation steps are consistent with (1) in Example 1.
[0094] (2) The same SLM process as step (2) of Example 1 is used to prepare a bulk alloy.
[0095] (3) Perform annealing heat treatment on the printed alloy in the same manner as step (3) of Example 1.
[0096] The Co-Cr-Fe-Ni based ODS high entropy alloy has good bulk forming performance, a density of 98.0%, and a hardness of 273.3 HV. The microstructure of the alloy is similar to that of Example 1, and a large number of Y2Ti2O7 nanoparticles are dispersed in the matrix.
[0097] Example 6
[0098] (1) Using Co-Cr-Fe-Ni high entropy pre-alloyed powder with equal atomic ratios of each element, Fe-Y pre-alloyed powder containing 6.0wt.% Y element, and TiO2 powder as raw materials, the required powders are weighed according to a ratio of 98.5wt.% Co-Cr-Fe-Ni, 0.7wt.% Fe-Y, and 0.8wt.% TiO2, and the weighed powders are mixed and poured into a stainless steel ball mill with a volume of 500ml (400g of mixed powder per mill); the remaining preparation steps are consistent with (1) in Example 1.
[0099] (2) The same SLM process as step (2) of Example 1 is used to prepare a bulk alloy.
[0100] (3) Perform annealing heat treatment on the printed alloy in the same manner as step (3) of Example 1.
[0101] The Co-Cr-Fe-Ni based ODS high entropy alloy has good bulk forming performance, a density of 98.9%, and a hardness of 266.7 HV. The microstructure of the alloy is similar to that of Example 1, and a large number of Y2Ti2O7 nanoparticles are dispersed in the matrix.
[0102] Example 7
[0103] (1) Prepare raw material mixed powder and perform pre-printing preparation in the same manner as step (1) of Example 1.
[0104] (2) The same SLM process as step (2) of Example 1 is used to prepare a bulk alloy.
[0105] (3) Each ODS high entropy alloy block material prepared by SLM was annealed in a tube furnace under argon protection. The annealing temperature was 800°C, the holding time was 2h, and the heating rate was set to 10°C / min.
[0106] The Co-Cr-Fe-Ni based ODS high entropy alloy has good bulk forming performance, a density of 98.1%, and a hardness of 266.2 HV. The microstructure of the alloy is similar to that of Example 1, and a large number of Y2Ti2O7 nanoparticles are dispersed in the matrix.
[0107] Example 8
[0108] (1) Prepare raw material mixed powder and perform pre-printing preparation in the same manner as step (1) of Example 1.
[0109] (2) The same SLM process as step (2) of Example 1 is used to prepare a bulk alloy.
[0110] (3) Each ODS high entropy alloy block material prepared by SLM was annealed in a tube furnace under argon protection. The annealing temperature was 950°C, the holding time was 1h, and the heating rate was set to 15°C / min.
[0111] The Co-Cr-Fe-Ni based ODS high entropy alloy has good bulk forming performance, a density of 98.7%, and a hardness of 274.4 HV. The microstructure of the alloy is similar to that of Example 1, and a large number of Y2Ti2O7 nanoparticles are dispersed in the matrix.
[0112] Comparative Example 1
[0113] The specific implementation steps of this comparative example are as follows:
[0114] (1) Co-Cr-Fe-Ni high entropy pre-alloyed powder and Y2O3 powder with equal atomic ratios of each element are used as raw materials. The required powders are weighed according to the ratio of 99.5wt.% Co-Cr-Fe-Ni and 0.5wt.% Y2O3. The weighed powders are mixed and poured into a stainless steel ball mill with a volume of 500ml (400g mixed powder per can). After the ball mill is sealed, it is vacuumed using a vacuum pump, and then filled with 0.1MPa argon as a protective gas without adding any grinding balls or process control agents. Then a planetary ball mill is used to operate at a speed of 200rpm for 6h so that the various powders in the mixed powder can be evenly mixed, thereby obtaining a raw material mixed powder for the SLM process. The raw material mixed powder is placed in a vacuum drying oven and kept warm at a temperature of 120℃ for 20h, and then the raw material mixed powder is taken out and poured into the powder feeding bin of the printing device and flattened. A 100 mm × 100 mm stainless steel substrate was installed in the printing device and preheated to 120°C.
[0115] (2) The same SLM process as step (2) of Example 1 is used to prepare a bulk alloy.
[0116] (3) Perform annealing heat treatment on the printed alloy in the same manner as step (3) of Example 1.
[0117] It has been determined that the high entropy alloy block has good forming performance. Figure 4 The scanning electron microscope (SEM) photo of the alloy after aqua regia corrosion shows that Y2O3 is aggregated to the micron level, which does not achieve the effect of dispersion strengthening. Since Y2O3 powder and Co-Cr-Fe-Ni high entropy pre-alloyed powder are directly used as raw materials for printing, Y2O3 has a high melting point and cannot be fully melted into the SLM molten pool, and agglomerates during the SLM melting and solidification process. However, the Co-Cr-Fe-Ni high entropy pre-alloyed powder, Fe-Y pre-alloyed powder, and nano-TiO2 powder provided by the present invention are used as raw materials, and each powder is fully melted, wherein a part of Y, Ti, and O elements directly react in situ during the solidification cooling process to form a Y-Ti-O composite oxide with higher thermal stability than Y2O3, and subsequent annealing promotes the further progress of the in-situ reaction, and finally achieves the dispersion distribution of fine-sized nano-oxide particles.
[0118] Comparative Example 2
[0119] The specific implementation steps of this comparative example are as follows:
[0120] (1) Prepare raw material mixed powder and perform pre-printing preparation in the same manner as step (1) of Example 1.
[0121] (2) The same SLM process as step (2) of Example 1 is used to prepare a bulk alloy.
[0122] The results show that the high entropy alloy has good bulk forming performance, but the number density of oxide particles in the matrix is only 4.8×10 20 m -3 , which is two orders of magnitude lower than that of Example 1. If the bulk alloy prepared by SLM printing is not annealed, more Y, Ti, and O elements cannot be precipitated in situ from the matrix in the form of nano-oxide particles, resulting in a low number density of oxide particles in the matrix, which cannot meet the requirements.
[0123] Comparative Example 3
[0124] The specific implementation steps of this comparative example are as follows:
[0125] (1) Co-Cr-Fe-Ni high entropy pre-alloyed powder with equal atomic ratios of each element, Fe-Y pre-alloyed powder containing 6.0wt.% Y element, and TiO2 powder are used as raw materials. The required powders are weighed according to the ratio of 99.6wt.% Co-Cr-Fe-Ni, 0.2wt.% Fe-Y, and 0.2wt.% TiO2. The weighed powders are mixed and poured into a stainless steel ball mill with a volume of 500ml (400g mixed powder per can). After the ball mill is sealed, it is vacuumed using a vacuum pump, and then filled with 0.1MPa argon as a protective gas without adding any grinding balls or process control agents. Then a planetary ball mill is used to operate at a speed of 200rpm for 6h so that the various powders in the mixed powder can be evenly mixed, thereby obtaining a raw material mixed powder for the SLM process. The raw material mixed powder is placed in a vacuum drying oven and kept warm at a temperature of 120℃ for 20h, and then the raw material mixed powder is taken out and poured into the powder feeding bin of the printing device and laid flat. A 100 mm × 100 mm stainless steel substrate was installed in the printing device and preheated to 120°C.
[0126] (2) The same SLM process as step (2) of Example 1 is used to prepare a bulk alloy.
[0127] (3) Perform annealing heat treatment on the printed alloy in the same manner as step (3) of Example 1.
[0128] The high entropy alloy block has good forming performance, but nano-scale oxide particles are almost undetectable in the matrix. Since the amount of Fe-Y powder and TiO2 powder used is less than the range of Fe-Y powder and TiO2 powder in the present invention, the Y-Ti-O composite oxide formed by the direct in-situ reaction of Y, Ti, and O elements during the solidification and cooling process is extremely small and can hardly be detected.
[0129] Comparative Example 4
[0130] The specific implementation steps of this comparative example are as follows:
[0131] (1) Co-Cr-Fe-Ni high entropy pre-alloyed powder with equal atomic ratios of each element, Fe-Y pre-alloyed powder containing 6.0wt.% Y element, and TiO2 powder are used as raw materials. The required powders are weighed according to the ratio of 99.6wt.% Co-Cr-Fe-Ni, 5.0wt.% Fe-Y, and 5.0wt.% TiO2. The weighed powders are mixed and poured into a stainless steel ball mill with a volume of 500ml (400g mixed powder per can). After the ball mill is sealed, it is vacuumed using a vacuum pump, and then filled with 0.1MPa argon as a protective gas without adding any grinding balls or process control agents. Then a planetary ball mill is used to operate at a speed of 200rpm for 6h so that the various powders in the mixed powder can be evenly mixed, thereby obtaining a raw material mixed powder for the SLM process. The raw material mixed powder is placed in a vacuum drying oven and kept warm at a temperature of 120℃ for 20h, and then the raw material mixed powder is taken out and poured into the powder feeding bin of the printing device and laid flat. A 100 mm × 100 mm stainless steel substrate was installed in the printing device and preheated to 120°C.
[0132] (2) The same SLM process as step (2) of Example 1 is used to prepare a bulk alloy.
[0133] (3) Perform annealing heat treatment on the printed alloy in the same manner as step (3) of Example 1.
[0134] It has been determined that the high entropy alloy block has good forming performance, but the oxide particles in the matrix are obviously agglomerated and the size reaches the micron level, which does not achieve the effect of dispersion strengthening. Since the amount of Fe-Y powder and TiO2 powder used is greater than the range of Fe-Y powder and TiO2 powder in the present invention, the amount of Y-Ti-O composite oxide formed by direct in-situ reaction of Y, Ti, and O elements during the solidification and cooling process is too large, which makes it easy for the nanoparticles to contact each other and agglomerate.
[0135] Comparative Example 5
[0136] The specific implementation steps of this comparative example are as follows:
[0137] (1) Prepare raw material mixed powder and perform pre-printing preparation in the same manner as step (1) of Example 1.
[0138] (2) The same SLM process as step (2) of Example 1 is used to prepare a bulk alloy.
[0139] (3) Each ODS high entropy alloy block material prepared by SLM was annealed in a tube furnace under argon protection. The annealing temperature was 700°C, the holding time was 1h, and the heating rate was set to 10°C / min.
[0140] It has been determined that the number density of oxide particles in the high entropy alloy block is only 8.9×10 20 m -3 , which is two orders of magnitude lower than that of Example 1. This is because the annealing temperature is lower than the range of the present invention and cannot provide enough energy to fully precipitate the nanoparticles in situ.
[0141] Comparative Example 6
[0142] The specific implementation steps of this comparative example are as follows:
[0143] (1) Prepare raw material mixed powder and perform pre-printing preparation in the same manner as step (1) of Example 1.
[0144] (2) The same SLM process as step (2) of Example 1 is used to prepare a bulk alloy.
[0145] (3) Each ODS high entropy alloy block material prepared by SLM was annealed in a tube furnace under argon protection. The annealing temperature was 1000°C, the holding time was 1h, and the heating rate was set to 10°C / min.
[0146] It has been determined that the average size of the oxide particles in the high entropy alloy block is above 80 nm, which is significantly larger than that in Example 1. This is because the annealing temperature is higher than the range of the present invention, resulting in rapid growth of the oxide particles.
[0147] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A Co-Cr-Fe-Ni based ODS high entropy alloy, characterized in that: The Co-Cr-Fe-Ni series ODS high entropy alloy is obtained by SLM forming a mixed raw material powder consisting of Co-Cr-Fe-Ni high entropy pre-alloy powder, Fe-Y powder and TiO2 powder; The elements Co, Cr, Fe and Ni in the Co-Cr-Fe-Ni high entropy pre-alloyed powder are in equal atomic ratios; Among the raw materials, the proportion of Fe-Y powder is 0.7-2.0wt.%, the proportion of TiO2 powder is 0.8-2.4wt.%, and the proportion of Co-Cr-Fe-Ni high entropy pre-alloyed powder is 95.6-98.5wt.%.
2. The Co-Cr-Fe-Ni based ODS high entropy alloy according to claim 1, characterized in that: The content of Y element in the Fe-Y powder is 6.0 wt.%.
3. The method for preparing the Co-Cr-Fe-Ni based ODS high entropy alloy according to claim 1 or 2, characterized in that: The following steps are involved: Step S1: Co-Cr-Fe-Ni high entropy pre-alloyed powder, Fe-Y powder and TiO2 powder are used as raw materials and mixed to obtain a mixed powder; Step S2: forming the mixed powder by SLM printing and annealing to obtain the Co-Cr-Fe-Ni based ODS high entropy alloy.
4. The preparation method according to claim 3, characterized in that: In the step S2, the annealing gas is an inert gas, and the inert gas is selected from at least one of argon, helium, and neon; The annealing temperature is 800-950°C and the annealing time is 1-2h; The heating rate of the annealing is 10-15°C / min.
5. The preparation method according to claim 3, characterized in that: In the step S2, the mixed powder is dried before SLM printing; The drying temperature is 120-130° C., and the drying time is 20-30 hours.
6. The preparation method according to claim 3, characterized in that: In step S2, the process parameters of the SLM printing are set as follows: the powder layer thickness is a fixed value of 40 μm, the scanning mode is a layer-by-layer rotation of 67°, the laser power is 200-300 W, the scanning interval is 70-80 μm, and the scanning speed is 600-1200 mm / s.
7. The preparation method according to claim 3, characterized in that: In the step S2, the substrate formed by SLM printing is a stainless steel substrate, and the size of the substrate is 100 mm×100 mm; The substrate is preheated to 120° C. before printing, and then vacuumed and filled with argon gas for protection. Printing is not started until the oxygen content drops below 0.01%.
8. The preparation method according to claim 3, characterized in that: In step S1, a planetary ball mill is used for mixing, and no grinding balls or process control agents are added to the ball mill; The rotation speed of the planetary ball mill is 200 rpm to 250 rpm, and the operation time is 4 to 6 hours.
9. The preparation method according to claim 3, characterized in that: In the step S1, the protective gas during the mixing is argon gas, and the amount of the argon gas is 0.1MPa to 0.15MPa.
10. Application of the Co-Cr-Fe-Ni based ODS high entropy alloy as described in claim 1 or 2, or the Co-Cr-Fe-Ni based ODS high entropy alloy prepared by the preparation method according to any one of claims 3 to 9 in the fields of metal-based composite materials, aerospace, new energy, and biomedicine.
Citation Information
Patent Citations
Method for preparing high-toughness eutectic high-entropy alloy based on selective laser melting technology
CN112935252A
Nano / submicron double-scale oxide reinforced refractory high-entropy alloy composite material and preparation method thereof
CN115679177A
Method of enhancing hardness and wear resistance of high entropy alloys
KR1020170110284A
High-entropy alloy for use as a base material in a powder bed fusion process
WO2023037018A1
Cited By
Method for preparing high-performance low-cost CoCrNi-TiC high-entropy alloy composite material through 3D printing
CN121061172A